2018
DOI: 10.5650/jos.ess17275
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Sodium Dodecyl Sulfate on Tetrahydrofuran-Assisted Methane Hydrate Formation

Abstract: Sodium dodecyl sulfate (SDS) markedly improved tetrahydrofuran (THF) - assisted methane hydrate formation. Firstly, methane hydrate formation with different THF amount, 1, 3, and 5.56 mol%, was studied. SDS with 1, 4, and 8 mM was then investigated for its roles on the methane hydrate formation with and without THF. The experiments were conducted in a quiescent condition in a fixed volume crystallizer at 8 MPa and 4°C. The results showed that almost all studied THF and SDS concentrations enhanced the methane h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…On the other hand, simultaneous usage of SDS (0.05 wt%) in aq-THF (5 mol%) in THF + CO 2 hydrates allows faster nucleation and a significant increase in gas storage capacity [44]. Interestingly SDS also helps in promoting the methane gas uptake in hydrates formed with lesser mol% THF, e.g., the gas uptake is 129.6 mmol/mol, while there is no gas consumption in this system in the absence of SDS [26]. As noticed in the present study the gas uptake remained same in THF + CH 4 system with or without SDS.…”
Section: Methane Uptake At Higher Pressurementioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, simultaneous usage of SDS (0.05 wt%) in aq-THF (5 mol%) in THF + CO 2 hydrates allows faster nucleation and a significant increase in gas storage capacity [44]. Interestingly SDS also helps in promoting the methane gas uptake in hydrates formed with lesser mol% THF, e.g., the gas uptake is 129.6 mmol/mol, while there is no gas consumption in this system in the absence of SDS [26]. As noticed in the present study the gas uptake remained same in THF + CH 4 system with or without SDS.…”
Section: Methane Uptake At Higher Pressurementioning
confidence: 94%
“…We used THF in stoichiometry (5.66 mol%) for sII for the following reasons: it is well-known that under these conditions the hydrate system is known to have the highest thermodynamic stability [16,[23][24][25] and also the thermal stability at 0.1 MPa is very high [14]. However, recently some studies using a lesser amount of THF indicated relatively higher methane gas uptake [14,26,27] and also at much lower THF (1.0 mol %) methane gas consumption is negligible, particularly in the absence of constant stirring [26]. However, experiments conducted with continuous stirring have shown significant gas consumption due to the phase change even with lower THF concentrations [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…The schematic of the gas hydrate experimental setup is presented in Figure 1. The details of the description were presented in the work of Siangsai et al [21] and Siangsai et al [22]. Briefly, the methane hydrate experimental apparatus contained the crystallizer.…”
Section: Apparatus For the Hydrate Formation And Dissociation Experimmentioning
confidence: 99%
“…The methane uptake was calculated using the pressure and temperature data recorded during the hydrate formation experiment. The detail of the calculation of gas consumption during the hydrate formation was presented in the works of Inkong et al [23], Inkong et al [24], and Siangsai et al [22].…”
Section: Hydrate Formationmentioning
confidence: 99%
See 1 more Smart Citation